Adherence level and medication beliefs among care homes residents in Klang Valley / Hasnah Ismail ... [et al.] - Ismail, Hasnah; Wan Azmi, Wan Uswah Hasanah; Loganathan, Mathumalar; Usir, Ezlina (Faculty of Pharmacy, 2021)
Medication adherence is a growing problem in a healthcare system especially among elderly. Elderly are often associated with co-morbidities that exposed them to poly-pharmacy, this eventually leads to poor adherence to medication. Medication beliefs have influenced the way the patients perceive the effectiveness of the medications and its negative outcomes. It is projected to be a strong predictor of medication non-adherence among patients. The objectives of this study were to investigate the level of medication adherence and the relationship between medication adherence and medication beliefs among elderly residing in care homes. The study was a crosssectional study involving elderly aged 65 years and above, currently taking at least one medication for chronic illness and have stayed for at least one year in the care homes. Twenty-seven care homes in Klang Valley involving 258 respondents were involved in this study. A validated questionnaire consisted of demographic data of respondents, Belief about Medicine Questionnaire, and Medication Safety Alert Tool for Elderly (MeSATE) were utilized. More than half (59.7%) of the elderly were identified as having a low risk to medication non-adherence. Statistically significant correlations were reported in specific concern (r = 0.273, p<0.001), general harm (r = 0.327, p<0.001) and general overuse (r = 0.134, p = 0.032) where it was positively correlated with higher risk of medication non-adherence. In conclusion, specific-concern, general-harm, and general-overuse on medication beliefs strongly predict the adherence level to medication.